The value of serial cervical length measurements for the prediction of threatened preterm labour - Sotiriadis, Alexandros; Kavvadias, Alexios; Papatheodorou, Stefania; Paraskevaidis, Evangelos A.; Makrydimas, George V. (My University, 2010)
Objectives: To assess the predictive performance of cervical length measurement at presentation and 24 h later in women with symptoms of preterm labour. Study design: Cervical length was measured transvaginally at presentation and 24 hours later in 122 women presenting with threatened preterm labour between 23 and 33 + 6 gestational weeks. Results: Six women delivered within 1 week of presentation. The sensitivity and specificity of a cervical length <15 mm at admission for delivery within one week was 83.3 and 95.8%, respectively. A reduction of >20% in cervical length 24 h after admission predicted 50% of preterm deliveries within 1 week, with a specificity of 92.7%; in combination with cervical length at presentation it did not improve the prediction. The same was observed for birth before 32 weeks (N = 9) and birth before 35 weeks (N = 15). Conclusions: Women with threatened preterm labour and a cervical length of <15 mm at presentation are at high risk of delivering preterm. Cervical change in the following 24 hours does not seem to improve the prediction.
Keywords: Cervical length; Cervix; Prediction; Preterm birth; Ultrasound